Efek Pemberian Priming Fentanil 1 Μg/Kgbb Terhadap Insidensi Batuk Pasca-Preemptif Analgesia Fentanil 2μg/KgBB di RSUP Dr. Sardjito - Prakosa, Nur Hamam; Uyun, Yusmein; Widyastuti, Yunita (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: Fentanyl is an opioid analgesic that is almost always used in patients undergoing general anesthesia. The use of intravenous fentanyl can cause a cough effect known as fentanyl-induced cough (FIC). Although there have been many studies conducted to reduce the incidence of cough after injection of fentanyl intravenously both pharmacologically and nonpharmacologically, standard therapy has not been established to prevent coughing. Method: Randomized clinical trial with double blindness. The sample was chosen using the non-probability sampling method in a consecutive manner until the sample was fulfilled. Age range 18-65 years, with ASA III physical status, non-active smokers undergoing elective surgery with general anesthesia at Dr. Sardjito General Hospital will be grouped into 2 groups, one group of a priming dose of fentanyl 1 μg/kgbb and the control group without priming dose of fentanyl. Both groups received total fentanyl 2 μg/kgbb with an injection speed of 0.5 cc per second. Data analysis to determine differences in the incidence of cough between the two treatment groups with outcomes in the form of mild cough, severe cough, or not coughing, then the chi-square test is used when the requirements are met. Secondary outcomes and side effects of fentanyl administration were also assessed.is performed Result. Incidence of fentanyl-induced cough (FIC) in the treatment group using priming dose of fentanyl 1 μg/kgbb was 2 patients (2.7%), while the incidence of cough in the group without priming dose of fentanyl was 11 patients (15.1%) with p = 0.009 meaning that there was a statistically significant difference. All patients with cough incidence were in the mild cough category, both in the priming dose of fentanyl group as many as 2 patients and 11 patients in group without priming dose of fentanyl. There is no statistically significant difference in the incidence of apnea, and bradycardia Conclusion. The use of 1 μg/kgbb priming dose of fentanyl can reduce the incidence of cough after fentanyl 2 μg/kgbb analgesia at an injection rate of 0.5 cc per second